Development of β-carotene enriched complementary flours using finger millet, mango, spirulina and sesame - Germaine Yadang; Basil Leva; Souriou Soufianou; Manga G. Mbassi; Hippolyte Tene Mouafo; Viviane Ruth Djuikwo (Next Research, 2026)

Building better homes for pollinators using native-based landscapes in new suburban developments - Mykayla Hagaman; Patrick J. Bohlen; Jennifer McNamara; Alessandra Pandolfi; David G. Jenkins; Victoria Cope; Basil V. Iannone (Urban Ecosystems, 2026)
Maintaining healthy pollinator communities is vital for both agricultural and natural ecosystems, but there are many threats to pollinator communities globally. Urbanization is a one of these major threats, but urban green spaces present opportunities for pollinator conservation. The effectiveness of designed urban landscapes in supporting pollinators largely depends upon plant selection and design, and there is an increasing emphasis on incorporating more native plants. To provide guidance on how landscape designs and plant selection influence pollinator communities in new residential developments, we compared floral visitors in two recently established neighborhoods: one with conventional landscaping consisting of turfgrass and mostly non-native ornamental plants, and one without turfgrass and mostly native plants. We recorded visual observations of insects visiting blooming flowers and identified 1,361 individuals from 88 different species. While floral abundance was similar between the two communities, pollinator abundance and diversity was 2–3 times higher in the native plant-dominant landscape, showing that plant species selection was more important than floral abundance. Pollinator communities in the conventional landscapes were a subset of the more diverse communities in the native-based landscapes. The short-term addition of potted flowering native plants to the two neighborhoods increased the observed pollinator diversity in the conventional landscapes. Our results show that incorporating diverse native plantings into new and expanding residential developments can lead to the rapid assembly of diverse, abundant pollinator communities.

Challenges and opportunities integrating remote sensing for mangrove conservation in Papua New Guinea's complex natural and human landscapes - Midhun Mohan; Ewane Basil Ewane; Lara G. Moussa; Michael S. Watt; Peter I. Macreadie; Christopher J. Owers; Daria Agnieszka Karpowicz; Ian Reuben; Willie Doaemo (Regional Studies in Marine Science, 2025)

Naturally deformed polymineralic rocks provide quantitative rheological information - Kyrsten L. Johnston; Laurel Goodwin; Basil Tikoff; Evan Earnest; Christine Gopon; Thomas G. Blenkinsop (Journal of Structural Geology, 2025)

Ecoregional patterns of protist communities in mineral and organic soils: assembly processes, functional traits and diversity of testate amoebae in Northern Eurasia - Jiahui Su; Yuri A. Mazei; Andrey N. Tsyganov; Natalia G. Mazei; Victor A. Chernyshov; Alexander A. Komarov; Kirill V. Babeshko; Edward A.D. Mitchell; Satoshi Shimano; Pavel Krasilnikov; Damir A. Saldaev; Basil N. Yakimov (Soil Biology and Biochemistry, 2025)

Eco-friendly structures for sustainable mangrove restoration - Midhun Mohan; Pandi P. Selvam; Ewane Basil Ewane; Lara G. Moussa; Emma F. Asbridge; Stacey M. Trevathan-Tackett; Peter I. Macreadie; Michael S. Watt; Lucy Gwen Gillis; Francoise Cabada-Blanco; Ian Hendy; Eben North Broadbent; et al. (Science of The Total Environment, 2025)

Continental‐Scale α ‐ and β ‐Diversity Patterns of Terrestrial Eukaryotic Microbes: Effect of Climate and Microhabitat on Testate Amoeba Assemblages in Eurasian Peatlands - Jiahui Su; Yuri A. Mazei; Andrey N. Tsyganov; Natalia G. Mazei; Victor A. Chernyshov; Alexander A. Komarov; Kirill V. Babeshko; Edward A. D. Mitchell; Satoshi Shimano; Damir A. Saldaev; Basil N. Yakimov (Journal of Biogeography, 2025)
Aim The role of environmental factors that shape the large‐scale distribution of eukaryotic microbes remains understudied. We aimed to disentangle the impacts of latitudinal and longitudinal gradients on the distribution of Sphagnum‐ dwelling testate amoebae in mires and to understand the influence of environmental factors related to both local habitats (hummock—lawn—hollows) and regional climates. Location A range from temperate to subarctic and from the European part to the Far East of Russia (51°–70°N, 32°–158°E). Taxon Testate amoeba (Arcellinida, Euglyphida, and Amphitremida). Methods We analysed the testate amoeba (TA) composition and abundance data from 816 samples collected in 75 peatlands. Linear mixed‐effects models and redundancy analysis were applied to determine the likely environmental drivers of TA α ‐ and β ‐diversity. Results We identified a significant reversed latitudinal gradient in α ‐diversity which negatively correlated with the mean annual temperature. This gradient is microhabitat‐specific, being prominent in lawn and hollow microhabitats, but not in hummocks. Longitude, which corresponds mainly to a gradient of precipitation seasonality, was a significant predictor of TA β ‐diversity, especially in hollows. Main Conclusions Our findings identify climatic factors (e.g., mean annual temperature and precipitation seasonality) as likely shaping the continental‐scale TA α ‐ and β ‐diversity patterns, emphasising the microhabitat‐specific nature of these relationships. The absence of pattern in hummocks is interpreted as evidence for a predominant microhabitat stress (i.e., low moisture and pH) in this habitat.

Stormwater ponds: Unaccounted environmental challenges of a widely-adopted best management practice in urban landscapes - Mary G. Lusk; Eban Z. Bean; Basil V. Iannone; Alexander J. Reisinger (Journal of Environmental Management, 2025)

Remote sensing-based mangrove blue carbon assessment in the Asia-Pacific: A systematic review - Abhilash Dutta Roy; Pavithra S. Pitumpe Arachchige; Michael S. Watt; Apoorwa Kale; Mollie Davies; Joe Eu Heng; Redeat Daneil; G.A. Pabodha Galgamuwa; Lara G. Moussa; Kausila Timsina; Ewane Basil Ewane; Kerrylee Rogers; et al. (Science of The Total Environment, 2024)

Multi-scale beta-diversity patterns in testate amoeba communities: species turnover and nestedness along a latitudinal gradient - Jiahui Su; Yuri A. Mazei; Andrey N. Tsyganov; Viktor A. Chernyshov; Natalia G. Mazei; Damir A. Saldaev; Basil N. Yakimov (Oecologia, 2024)

Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Cultivar blends: A strategy for creating more resilient warm season turfgrass lawns - Brianna Whitman; Basil V. Iannone; Jason K. Kruse; J. Bryan Unruh; Adam G. Dale (Urban Ecosystems, 2022)

Generation of typical meteorological years for 33 locations in Greece: adaptation to the needs of various applications - Harry D. Kambezidis; Basil E. Psiloglou; Dimitris G. Kaskaoutis; Dimitris Karagiannis; Kalliopi Petrinoli; Ariadne Gavriil; Kosmas Kavadias (Theoretical and Applied Climatology, 2020)

Removal of U(VI) from Aquatic Systems, Using Winery By-Products as Biosorbents: Equilibrium, Kinetic, and Speciation Studies - Vasileios A. Anagnostopoulos; Petros G. Koutsoukos; Basil D. Symeopoulos (Water, Air, & Soil Pollution, 2015)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Topically Applied Phospho-Sulindac Hydrogel is Efficacious and Safe in the Treatment of Experimental Arthritis in Rats - George Mattheolabakis; Gerardo G. Mackenzie; Liqun Huang; Nengtai Ouyang; Ka Wing Cheng; Basil Rigas (Pharmaceutical Research, 2013)

Case–control study of smoking and non-melanoma skin cancer - Dana E. Rollison; Michelle R. Iannacone; Jane L. Messina; L. Frank Glass; Anna R. Giuliano; Richard G. Roetzheim; Basil S. Cherpelis; Neil A. Fenske; Kristen A. Jonathan; Vernon K. Sondak (Cancer Causes & Control, 2012)

Biological and molecular characterization of laboratory mutants of Cercospora beticola resistant to Qo inhibitors - Anastasios A. Malandrakis; Anastasios N. Markoglou; Dimitra C. Nikou; John G. Vontas; Basil N. Ziogas (European Journal of Plant Pathology, 2006)

Characterization of Laboratory Mutants of Botrytis cinerea Resistant to QoI Fungicides - Anastasios N Markoglou; Anastasios A Malandrakis; Andreas G Vitoratos; Basil N Ziogas (European Journal of Plant Pathology, 2006)

Observed and modelled tidal currents in the New Zealand region - Basil R. Stanton; Derek G. Goring; Robert G. Bell (New Zealand Journal of Marine and Freshwater Research, 2001)
Tidal currents derived from current meter measurements are compared with the output from a barotropic tidal model of the New Zealand region. For the semi‐diurnal constituents there was very good agreement for the M 2 tide and good agreement for the S 2 tide. For the diurnal constituents (K l , O l ) it was found that as the amplitude of the constituents decreased so did both the model/observation agreement and the accuracy of the observed tidal ellipse parameters. Consequently it was not possible to decide whether differences arose through shortcomings in the model or in the data. However, the overall performance of the model as a prognostic tool for ocean tidal current simulation appears to be good.

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The effects of boreal vegetation and podzolic soils on hydrochemistry at Høylandet (mid-Norway) - Hamish A. Anderson; John D. Miller; Robert C. Ferrier; T. A. Bruce Walker; Derek C. Bain; Ruairi G. McMahon; Alan Hepburn; Moira Stewart; Basil F. L. Smith; James S. Anderson (Hydrobiologia, 1997)